Pengaruh Nama Toko terhadap Minat Beli Konsumen - Holif, Abdul (Keizai, 2022)
The purpose of this study was to determine whether the name of the store had an influence on the variable of buying interest in SHMG fashion and 35,000 Sampit fashion. This study uses quantitative methods, and the population presented is all customers who have come and bought at SHMG and all 35,000 Sampit, and the sample taken in this study was obtained from 100 respondents. Sampling using accidental sampling with purposive sampling method and data analysis of this study using multiple linear regression analysis. And this research instrument uses a questionnaire containing questions that will be given to respondents using Likert scale measurements to collect data about store name variables and buying interest. And the results of the study indicate that the store name variable does not have a significant effect on the buying interest variable. This means that even though the shop name is made to show that the shop name is cheap, this will not affect buying interest or will reduce buying interest.